Differential effects of heat-not-burn and conventional cigarettes on coronary flow, myocardial and vascular function - Ignatios Ikonomidis (Nature Portfolio, 2021)
Abstract We compared the effects of Heat-not-Burn cigarette (HNBC) to those of tobacco cigarette (Tcig), on myocardial, coronary and arterial function as well as on oxidative stress and platelet activation in 75 smokers. In the acute study, 50 smokers were randomised into smoking a single Tcig or a HNBC and after 60 min were crossed-over to the alternate smoking. For chronic phase, 50 smokers were switched to HNBC and were compared with an external group of 25 Tcig smokers before and after 1 month. Exhaled carbon monoxide (CO), pulse wave velocity (PWV), malondialdehyde (MDA) and thromboxane B2 (TxB2) were assessed in the acute and chronic study. Global longitudinal strain (GLS), myocardial work index (GWI), wasted myocardial work (GWW), coronary flow reserve (CFR), total arterial compliance (TAC) and flow-mediated dilation (FMD) were assessed in the chronic study. Acute HNBC smoking caused a smaller increase of PWV than Tcig (change 1.1 vs 0.54 m/s, p < 0.05) without change in CO and biomarkers in contrast to Tcig. Compared to Tcig, switching to HNBC for 1-month improved CO, FMD, CFR, TAC, GLS, GWW, MDA, TxB2 (differences 10.42 ppm, 4.3%, 0.98, 1.8 mL/mmHg, 2.35%, 19.72 mmHg%, 0.38 nmol/L and 45 pg/mL respectively, p < 0.05). HNBCs exert a less detrimental effect on vascular and cardiac function than tobacco cigarettes. Trial registration Registered on https://clinicaltrials.gov/ (NCT03452124, 02/03/2018).